Epidermodysplasia Verruciformis: A Case Report - Anisha Joshi; Bibush Amatya (Nepal Journal of Dermatology, Venereology & Leprology)
Epidermodysplasia verruciformis (EDV) is a rare, inherited disorder that is characterized by an increased susceptibility to infection with specific human papilloma viruses (HPV) and a greater propensity for developing malignant skin tumors.